2022
DOI: 10.2105/ajph.2022.306825
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Inequities in Paid Family and Medical Leave: United States, 2011 and 2017–2018

Abstract: Objectives. To examine racial and ethnic inequities in paid family and medical leave (PFML) access and the extent to which these inequities are mediated by employment characteristics. Methods. We used data from the 2011 and 2017–2018 American Time Use Survey in the United States to describe paid leave access by race/ethnicity. We present unadjusted models, models stratified by policy-targetable employment characteristics, and adjusted regression models. Results. We found that 54.4% of non-Hispanic White work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In our estimation of the use of PSL, we control for demographic and employment-related characteristics that have been found to be related to receipt and use of PSL,14,30 including sex/gender (male, female), race/ethnicity (Black non-Latino, Latino, other/multiracial non-Latino, or White non-Latino), education (high school degree or less, some college or associate's degree, bachelor's degree or more), age (18-35, 36-45, 46-55, and 56-64 years old), foreign-born status (US-born or foreign-born), presence of a spouse or partner in the household (yes, no), presence of children in the household (yes, no), and a logged income-to-needs ratio (continuous variable). The income-to-needs ratio is measured using total Supplemental Poverty Measure (SPM) resources (posttax cash income plus in-kind benefits, minus nondiscretionary work, childcare, and medical expenses), divided by the SPM poverty line, logged to account for greater effects of income at lower levels of income to needs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our estimation of the use of PSL, we control for demographic and employment-related characteristics that have been found to be related to receipt and use of PSL,14,30 including sex/gender (male, female), race/ethnicity (Black non-Latino, Latino, other/multiracial non-Latino, or White non-Latino), education (high school degree or less, some college or associate's degree, bachelor's degree or more), age (18-35, 36-45, 46-55, and 56-64 years old), foreign-born status (US-born or foreign-born), presence of a spouse or partner in the household (yes, no), presence of children in the household (yes, no), and a logged income-to-needs ratio (continuous variable). The income-to-needs ratio is measured using total Supplemental Poverty Measure (SPM) resources (posttax cash income plus in-kind benefits, minus nondiscretionary work, childcare, and medical expenses), divided by the SPM poverty line, logged to account for greater effects of income at lower levels of income to needs.…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29] While studies demonstrate the role of legislation in increasing PSL availability, research shows that PSL access continues to vary by race, income, employer type, and unionization status. 30,31 One study found that after the NYC law was passed, Latino workers were less likely to be aware of their new coverage. 32 These findings suggest a need to better understand unequal access to PSL and to assess whether such inequalities persist after new legislation is implemented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…67 Black women are also more likely to work in jobs that do not offer paid maternity leave. 102,103 Even within the same occupation, Black women can face additional breastfeeding barriers than White women, 104 including racist treatment from a supervisor. [104][105][106][107][108] Accordingly, the left side of our framework shows how, because of racism and unequal access to education and job opportunities, race is associated with employment, occupation, working conditions, and workplace breastfeeding experiences (Figure 1).…”
Section: Can Working Conditions Help Explain Racial Inequities In Bre...mentioning
confidence: 99%
“…67 Black women are also more likely to work in jobs that do not offer paid maternity leave. 102,103 Even within the same occupation, Black women can face additional breastfeeding barriers than White women, 104 including racist treatment from a supervisor. 104108…”
Section: Literature Reviewmentioning
confidence: 99%